Pregnancy‐related complications and risk of postpartum readmission for seizures and epilepsy: A national study. (12th August 2020) - Tantillo, Gabriela B.; Jetté, Nathalie; Yoo, Ji Yeoun; Stone, Joanne; Egerman, Marc; Dhamoon, Mandip S.
Abstract: Objective: Peripartum seizures remain a leading cause of maternal morbidity and mortality worldwide. Therefore, recognition of high‐risk individuals is essential. We aimed to determine the rate and identify risk factors for postpartum seizure/epilepsy readmissions. Methods: In this retrospective cohort study, the Nationwide Readmissions Database was used to identify index admissions for delivery and readmissions for seizures in the year 2013, defined by International Classification of Disease, Ninth Revision, Clinical Modification codes for epilepsy, convulsions, and eclampsia in the primary diagnostic position. Logistic regression analysis was used to examine 30‐day readmission for seizures as well as associations between demographic, medical, psychiatric, and pregnancy‐related factors. Results: There were 1 633 714 index admissions for delivery, with a 30‐day readmission rate for seizures/epilepsy of 19.69 per 100 000 index admissions. The mean age of index participants was 28.6 years (SD = 5.8). Postpartum 30‐day readmissions for eclampsia represented 80% of seizure/epilepsy readmissions. Higher income was associated with lower odds of seizure/epilepsy readmission (odds ratio [OR] = 0.50, 95% confidence interval [CI] = 0.34‐0.72, P = .03) for the highest income group. Eclampsia (OR = 19.9, 95% CI = 9.38‐42.2, P < .001), preexisting epilepsy (OR = 10.63, 95% CI = 6.43‐17.56, P < .001), pre‐eclampsia (OR = 3.23, 95% CI = 2.31‐4.51, P < .001), and gestational hypertension (OR = 2.78, 95% CI = 1.94‐3.98, P < .001) were associated with readmission for seizures. Significance: Readmissions for seizures are fortunately rare, but are important to minimize given morbidity and mortality. Most seizure readmissions occurring within 30 days postpartum were coded as eclampsia rather than convulsions or pre‐existing epilepsy. These findings suggest that early identification of women with pre‐eclampsia and eclampsia may play a role in the prevention of postpartum seizures. Women with these risk factors should be identified to optimize care and monitored closely for seizure‐associated complications.